2020
DOI: 10.3389/fcell.2020.00197
|View full text |Cite
|
Sign up to set email alerts
|

Human Obesity Induces Dysfunction and Early Senescence in Adipose Tissue-Derived Mesenchymal Stromal/Stem Cells

Abstract: Background: Chronic inflammatory conditions like obesity may adversely impact the biological functions underlying the regenerative potential of mesenchymal stromal/stem cells (MSC). Obesity can impair MSC function by inducing cellular senescence, a growth-arrest program that transitions cells to a pro-inflammatory state. However, the effect of obesity on adipose tissue-derived MSC in human subjects remains unclear. We tested the hypothesis that obesity induces senescence and dysfunction in human MSC. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 48 publications
9
77
0
1
Order By: Relevance
“…In rodents, even a relatively small number of senescent cells can cause long-lasting cellular dysfunction and spread to other tissues [ 118 ]. In humans, obesity triggers an early senescence program in adipose tissue-derived mesenchymal stromal/stem cells [ 119 ]. Moreover, both aging and diabetes mellitus share ER-stress-dependent senescence-associated dysfunctions such as atherosclerosis, coronary artery disease, insulin resistance and related metabolic anomalies, NAFLD, neurodegenerative diseases, osteoporosis, chronic kidney disease, peripheral vascular disease, periodontitis, impaired immune responses, frailty and sarcopenia [ 87 , 113 , 120 , 121 ].…”
Section: Cellular Senescence and Suppression Of Hsr In Chronic-degenementioning
confidence: 99%
“…In rodents, even a relatively small number of senescent cells can cause long-lasting cellular dysfunction and spread to other tissues [ 118 ]. In humans, obesity triggers an early senescence program in adipose tissue-derived mesenchymal stromal/stem cells [ 119 ]. Moreover, both aging and diabetes mellitus share ER-stress-dependent senescence-associated dysfunctions such as atherosclerosis, coronary artery disease, insulin resistance and related metabolic anomalies, NAFLD, neurodegenerative diseases, osteoporosis, chronic kidney disease, peripheral vascular disease, periodontitis, impaired immune responses, frailty and sarcopenia [ 87 , 113 , 120 , 121 ].…”
Section: Cellular Senescence and Suppression Of Hsr In Chronic-degenementioning
confidence: 99%
“…Such challenges are further compounded in screening for osteogenic effects by the long process required for both in vitro and in vivo functional assays—which range from several days for the ALP assay to several weeks and even months for mineralization assays—with the additional requirement of using primary cells with the capacity for osteogenesis. Indeed, one major reason for the conflicting reports of agonistic/antagonistic osteogenic properties of many compounds may be due to the quality of the primary MSCs used, since it is well documented that MSC senescence is related to a loss of osteogenic differentiation capacity while increasing adipogenic capacity ( Nuttall and Gimble, 2000 ; Moerman et al, 2004 ; Ho et al, 2013 ; Conley et al, 2020 ). We therefore sought to develop a rapid and robust in vitro platform for drug screening of osteogenic compounds based on our previous work on the proximal human Runx2 promoter, the master osteogenesis transcription factor, introduced into an immortalized, non-cancerous MSC cell line.…”
Section: Discussionmentioning
confidence: 99%
“…However, the existing data indicated that there were significant individual differences between the two types of cells. In addition, most studies have reported that obesity and age can significantly affect the differentiation ability of adipose derived stem cells, and whether there is an opposite effect for DAs has only been the subject of relatively few studies ( 41 , 42 ). As suggested in the present study, obesity may enhance the proliferation of DAs.…”
Section: Discussionmentioning
confidence: 99%